Dental trauma and oral health-related quality of life in schoolchildren from public schools of a southern Brazilian city - Abelardo Nunes LUNARDELLI; Sandra Espíndola LUNARDELLI; Keila Cristina Raush PEREIRA; Simone Costa XAVIER; Luiz Gustavo Teixeira MARTINS; Eliane Azevedo TRAEBERT; Jefferson TRAEBERT (Faculdade São Leopoldo Mandic, 2018)
Objective: To study the impact of dental trauma on the oral health-related quality of life among Brazilian students. Methods: A cross-sectional study involving a representative sample of students of the public schools (n = 435) in a city in southern Brazil was carried out. Data on dental trauma were collected through oral examinations using the O'Brien's criteria (1993) restricted to fractures and avulsions. The Brazilian version of the Oral Impacts on Daily Performances (OIDP) was used in order to collect data on the impact of oral health-related quality of life. Bivariate and multivariate analysis were performed through Poisson log-linear regression with robust estimator with significance levels set at p <0.05. Prevalence ratios (PR) and confidence intervals (95%) were estimated. Results: The prevalence of dental trauma was 7.2%, and it was associated with the following dimensions: performing daily activities [(PR = 3.52 (95% CI, 1.06-11.75)] (p = 0.040), and speaking [(PR = 3.67 (95% CI, 1.24-10.86)] (p = 0.019) after adjusting for sex, age, dental caries and malocclusion. Conclusion: The prevalence of dental trauma found among this population was low, but significantly associated with oral health-related quality of life.